KONTROVERSI ISLAMISASI ILMU PENGETAHUAN TINJAUAN PEMIKIRAN ISMAIL RAJI ALFARUQI DAN IMPLEMENTASI ILMU PENGETAHUAN TERHADAP PESERTA DIDIK - mulyadi, nanang; Mulyani, Yayu; Mutaqin, Mumu Zainal; Arifin, Muhammad (Institut Agama Islam Sahid (INAIS) Bogor, 2025)
This study aims to examine the controversy surrounding the Islamization of Science through the thoughts of Ismail Raji Al-Faruqi and its implementation in Islamic education. The main focus of this study is how the Islamization of Science can overcome the dualism between Islamic values ​​and the influence of Western secularism, especially in curriculum development and student character. Al-Faruqi emphasized the importance of integrating rational and divine knowledge to build an Islamic education system, which can produce an intelligent, faithful, and noble generation. By freeing knowledge from secularism and directing it toward a monotheistic orientation, students are expected to become perfect human beings capable of contributing to Islamic civilization. This study uses a qualitative approach with literature review to analyze Al-Faruqi's thoughts and the concept of Islamic epistemology in the reconstruction of knowledge based on revelation and reason. The discussion in this study also highlights the challenges and opportunities in implementing the Islamization of Science in the modern era, as well as its relevance in shaping an Islamic education paradigm that is responsive to the dynamics of the times without neglecting its Islamic identity. The implementation of this paradigm for students is realized through the integration of monotheistic values ​​in every discipline of science, the development of analytical thinking skills rooted in Islamic ethical principles, and the internalization of educational goals that place science as a means of self-actualization and devotion to Allah SWT.